A Dimeric π‐Stacking of Anthracene Inducing Efficiency Enhancement in Solid‐State Fluorescence and Non‐Doped Deep‐Blue Triplet–Triplet Annihilation Organic Light‐Emitting Diodes. Issue 17 (3rd June 2021) - Nalaoh, Phattananawee; Sungworawongpana, Nathas; Chasing, Pongsakorn; Waengdongbung, Wijitra; Funchien, Patteera; Kaiyasuan, Chokchai; Sudyoadsuk, Taweesak; Promarak, Vinich
Abstract: Triplet–triplet annihilation (TTA) mechanism utilizing the conversion of low triplet energy excitons to generate singlet excitons has been successfully employed in realizing highly efficient fluorescent organic light‐emitting diodes (OLEDs). Herein, new anthracene‐based TTA molecules (TPNACN and TPBACN ) are developed as deep‐blue emitters for high‐efficiency non‐doped TTA‐OLEDs. Their structural, physical, and photophysical properties are experimentally and theoretically investigated. These compounds in solid‐state exhibit different photophysical properties due to a discrepancy in the molecular packing. Particularly, in the crystal of TPNACN, anthracene moieties are arranged with dimeric π–π stacking, and the material shows a strong excimer emission in the deep‐blue region with ΦPL close to the ideal theoretical value. The non‐doped TTA‐OLED based on TPNACN attains a high maximum external quantum efficiency of 7.89% (6.63 cd A −1 ) with a low turn‐on voltage of 2.6 V, and displays deep‐blue emission with CIE coordinates of (0.146, 0.101). These results prove that a separated dimeric π‐stacked molecular alignment of anthracene enhances not only the fluorescence efficiency in the solid state but also the ratio of singlet exciton harvested by the TTA process in the device, bringing about excellent device electroluminescent properties. This can be a new tactic to designing new emissive materials for efficient OLED devices. Abstract : New deep‐blue anthracene‐based triplet–triplet annihilation (TTA) emitter with a unique dimeric π–π stacking of anthracene units in the solid‐state exhibits an enhancement in both solid‐state photoluminescence efficiency of the molecule and singlet exciton harvested by the TTA process in the device for achieving high efficiency non‐doped deep‐blue TTA organic light‐emitting diodes.